Lysine Biosynthesis in Streptomyces lipmanii: Implications in Antibiotic Biosynthesis - Kirkpatrick, J. R. (1973)
Streptomyces lipmanii produces two β-lactam antibiotics, penicillin N and 7-(5-amino-5-carboxyvaleramido)-7-methoxycephalosporanic acid. Both antibiotics contain α-aminoadipic acid side chains. In similar antibiotics produced by certain fungi, the α-aminoadipoyl moiety is derived from an intermediate in lysine biosynthesis. Our findings indicate, however, that in S. lipmanii, lysine is synthesized via α, ε-diaminopimelic acid—an entirely different biosynthetic route. This finding suggests not only a unique mechanism for the derivation of α-aminoadipate, but also that the system may be particularly amenable to genetic manipulation.